LEARNING INNOVATION OF ISLAMIC RELIGIOUS EDUCATION TECHNOLOGICAL APPROACH: IMPLICATIONS FOR ISLAMIC EDUCATION IN GORONTALO - Lestari, Anugrah; Fahri Yasin, Mohammad; Avelina, Gesika (EDUCATE : Jurnal Teknologi Pendidikan, 2026)
This study aims to map the trend of technology-based learning innovations in Islamic Religious Education learning and examine its implications for Islamic education in Gorontalo. The Systematic Literature Review research method is applied by following the PRISMA protocol, through Google Scholar, Garuda, SINTA, and DOAJ for the period 2020-2026. The search yielded 34 articles, consisting of 21 articles from reputable national sources (SINTA 2-5) and 13 national articles. The results of the study show that the innovation trend on the topic of Islamic Cultural History dominates literature (29%), the subject of Al-Qur’an Hadith is the least researched topic (9%). In terms of the innovation component, the tendency is towards gamification-based learning media through Kahoot, Quizizz, and Blooket and others, while innovation at the policy and curriculum level is still very limited. By implication, innovation in Islamic education in Gorontalo already has a digital foundation through the Madrasah Digital Report and the Pusaka application, but its use for pedagogical innovation in PAI subjects, especially the Qur’an Hadith, is still lacking and can be further developed. This study concludes that future development needs to go beyond media-centered classroom practices towards the integration of structured policies and curricula